The influence of institutional quality on human development : evidence from developing countries - Kamalu, Kabiru; Wan Hakimah Wan Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2022)
The paper evaluates the influence of institutional quality on human development in 14 developing countries using data over 1991-2019. We employed the Dynamic Common Correlated Effect method that accounts for heterogeneity and cross-sectional dependency associated with panel data, due to unobserved common factors. The findings revealed the evidence of positive and statistically significant long run effect of institutional quality on human development. In addition, financial development was found to promote human development whereas higher military expenditure negatively affected it in the long run. The results suggest that institutional quality promotes long run human development. Policymakers should nurture and develop institutions that have good quality such as deterring corruption, improving quality regulation and the application of the rule of law.